Multiplane and Spectrally-Resolved Single Molecule Localization Microscopy with Industrial Grade CMOS cameras - Babcock, Hazen P. (Sci Rep, 2018)
This work explores the use of industrial grade CMOS cameras for single molecule localization microscopy (SMLM). We show that industrial grade CMOS cameras approach the performance of scientific grade CMOS cameras at a fraction of the cost. This makes it more economically feasible to construct high-performance imaging systems with multiple cameras that are capable of a diversity of applications. In particular we demonstrate the use of industrial CMOS cameras for biplane, multiplane and spectrally resolved SMLM. We also provide open-source software for simultaneous control of multiple CMOS cameras and for the reduction of the movies that are acquired to super-resolution images.